Empirical force-field and ab initio calculations on delocalized open chain cations - Clark, Timothy; Schleyer, Paul; et al. (Journal of Computational Chemistry, 1997)
Allyl cation geometries optimized using an extended version of MMP2, newly parameterized for localized and delocalized classical cations, compare favorably with those obtained at the MP2(full)/6-31G* level. Hence, the force field should provide good starting structures for ab initio calculations. The pi-electron densities obtained by these two very different methods are quite similar. The relative energies of various isomers at MP4/6-31G*//MP2(full)/6-31G* are reproduced well by the force-field calculations. The heats of formation calculated by MMP2, as well as those predicted from the ab initio-data, agree with experimentally determined values. The force-field method provides interpretive capabilities. Energy differences between isomers can be separated into electronic and steric contributions, reasonable estimates of resonance energies are given, and nonbonded resonance energies in delocalized cations can be evaluated. The stabilizing 1-3 pi-interactions in allyl cations are quite significant, but are reduced by alkyl, groups hyperconjugatively and sterically. (C) 1997 by John Wiley & Sons, Inc.